Síntese de compostos com potenciais atividades biológicas ou magnéticas - Valeria Cristina da Costa (2008)
This thesis is divided in two parts and presents the results of our studies on the synthesis and the study of biological or magnetic proprieties of a series of ligands and their transition metalcomplexes. Firstly we prepared a series of dithiacarboxilic acids and their metal complexes to investigate the biological activity of these compounds against fungi, bacteria and cancerous cells.3,6-dithiaoctanedioic acid, (CH2SCH2COOH)2 (1), 3,7-dithia nenanodioic acid CH2(CH2SCH2COOH)2 (2) and 4,8-dithiaundecanedioic acid CH2(CH2S(CH2)2COOH)2 (3) were prepared and characterized by analytical data, infrared and NMR spectroscopies (1H and 13C).Metal complexes of these ligands with Pt(II), Cu(II), Co(II) and Ni(II) were prepared and their structures, proposed on the basis of analytical and infrared spectroscopy. Compounds 1 and 2 are active against Streptococus pyogenes bacterium and 2 is also active against the Candida albicans, Candida glabrata and Candida krusei fungi. Unfortunately the activity of the metal complexes could not be investigated because they are completely insoluble in water and in a variety of organicsolvents. In the second part we describe the preparation of a series of bimetallic chains of the type [ML][Fe(III)Tp(CN)3]2 were M = Ni(II), Co(II), Cu(II) or Mn(II); L = 3,3-3,3- diaminodipropylamine (dipta), diethylenetriamine (dien) or pentamethyldiethylenetriamine(pmedien) and Tp = ion hydrotris(1-pyrazolyl)borate. The crystalline chain[Nidipta][Fe(III)Tp(CN)3]2 (19) was characterized by elemental analysis and infrared spectroscopy. The molecular structure of 19 was determined by X-ray diffraction on single crystals. Compound 19 is a zigzag chain with regular alternating bis-monodentate [Fe(1)Tp(CN)3]2- units and[Ni(dipta)]2+ cations, the six coordination around the nickel atom being achieved by the coordination of another [Fe(2)Tp(CN)3]2- group acting as a monodentate end-cap ligand. Magnetic properties have been investigated in the temperature range 1.9-300 K. MT at 300 K is 2.60cm3 mol-1 K, a value which is as expected for a spin triplet from the octahedral nickel(II) ion and two spin doublets from two low-spin iron(III) centers with an important orbital contribution which are magnetically isolated. The magnetic susceptibility of 19 becomes field dependent for T < 8.0 K. The presence of a maximum of susceptibility, which occurs at 3.8 K under an applied magnetic field of 800 G, is indicative of a weak antiferromagnetic interaction between the ferromagneticchains of 19. This maximum disappears for H 700 G suggesting a field induced transition from an antiferromagnetic to a ferromagnetic state, that is, a metamagnetic behavior that may be understood as a result of weak dipolar interactions between the ferromagnetic chains of 19